2019
DOI: 10.3389/fphys.2019.01467
|View full text |Cite
|
Sign up to set email alerts
|

Yes-Associated Protein 1 Plays Major Roles in Pancreatic Stellate Cell Activation and Fibroinflammatory Responses

Abstract: Background: Yes-associated protein 1 (YAP), a transcriptional co-activator and major effector of the Hippo pathway, regulates cell differentiation and morphology in many cell types and supports aberrant tumor growth. Recent studies showed that YAP is expressed in pancreas tissues in pancreatic ductal adenocarcinoma (PDAC) patients and experimental models of PDAC, with YAP largely found in cancer cells and pancreatic stellate cells (PaSC) in the stroma.Methods and Results: We studied here the role of YAP in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 63 publications
4
11
0
Order By: Relevance
“…In addition, western blot results showed that the diabetic aorta treated with LX exhibited less COL1, which accounted for 65% of the total collagen in the normal vessel [90] (Figure 4F). In vitro [92]. This is in line with literature showing that YAP signalling plays a role in extracellular matrix remodelling, especially in regulating collagen production [92].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, western blot results showed that the diabetic aorta treated with LX exhibited less COL1, which accounted for 65% of the total collagen in the normal vessel [90] (Figure 4F). In vitro [92]. This is in line with literature showing that YAP signalling plays a role in extracellular matrix remodelling, especially in regulating collagen production [92].…”
Section: Discussionsupporting
confidence: 84%
“…In vitro [92]. This is in line with literature showing that YAP signalling plays a role in extracellular matrix remodelling, especially in regulating collagen production [92].…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, the plasma sEV-associated proteins ( Figure 3B,C) identified in plasma with AUC ≥ 0.7 case:control classifier performance in both the LUAD and PDAC cohorts denote a pan-adenocarcinoma sEV signature and suggest intriguing implications regarding markers that yield insight into cancer-host interchange within the tumor microenvironment. For example, PDGF (Platelet-derived growth factor subunit A) has been shown to be involved in recruitment and activation of cancer-associated fibroblasts in lung adenocarcinoma [31] and to also exert similar effect on pancreatic stellate cells and fibroblasts in PDAC tumors [32,33]. Tumor derived VEGFC (Vascular endothelial growth factor C) has been demonstrated to support metastatic expansion of primary tumors into the lymphatic vasculature in many tumor types, challenging the traditional concept of a purely passive role of the lymphatic vessels in cancer metastasis [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors of the MAPK pathway, such as p38, reduce YAP levels in the PSC. YAP knockdown inhibits the activation of Akt and ERK and also suppresses the expression of fibrous and inflammatory proteins both with and cytes [54]. Quiescent PSCs have receptors for cholecystokinin, and upon binding, they react with the release of acetylcholine, which in turn acts on cells of the pancreatic acinus [55].…”
Section: Molecular Mediators Involved In Activity Of Pancreatic Stellate Cellsmentioning
confidence: 99%